2013
DOI: 10.1371/journal.pone.0078061
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Bambusae Caulis in Taeniam Inhibits PMA-Induced Tumor Cell Invasion and Pulmonary Metastasis: Suppression of NF-κB Activation through ROS Signaling

Abstract: Bamboo shavings (Bambusae Caulis in Taeniam, BCT) are widely used as a traditional Chinese medicine to control hypertension and cardiovascular disease, and to alleviate fever, vomiting, and diarrhea. It has been demonstrated that BCT reduces ovalbumin-induced airway inflammation by regulating pro-inflammatory cytokines, and decreases tumor growth in tumor-bearing mice. However, the effects of BCT on the metastatic potential of malignant cancer cells and the detailed mechanism of its anti-metastatic activity ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…The ability of cells to migrate to the wounded area was assessed as described previously52. Briefly, 90% confluent cells on 60 mm culture dishes were treated with mitomycin C (25 μg/mL) for 30 min and wounded by scraping.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of cells to migrate to the wounded area was assessed as described previously52. Briefly, 90% confluent cells on 60 mm culture dishes were treated with mitomycin C (25 μg/mL) for 30 min and wounded by scraping.…”
Section: Methodsmentioning
confidence: 99%
“…After floating cell debris was washed away, complete culture medium was added, and cell migration in the presence or absence of ELH was monitored. Cell migration and invasion across a Transwell chamber with a 6.5 mm diameter and an 8 μm pore polyethylene tetraphthalate (PET) membrane (SPL Lifesciences, Korea) were measured as described previously52.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliquots of protein resolved by SDS-PAGE were immunoblotted with specific antibodies and detected as described previously2223.…”
Section: Methodsmentioning
confidence: 99%
“…The material media of past dynasties in Chinese history indicated that BC was used to treat fever, diarrhea, and chest inflammation. [20][21][22] Accordingly, Ministry of Health in China approved BC as an ethnopharmacological functional food material. Other study demonstrated BC's anti-inflammatory effects with anti-oxidative properties.…”
Section: Introductionmentioning
confidence: 99%